Developing An E-Module Using Music Therapy Method To Prevent Speech Delay In Children Aged 3-5 Years At Klambir V Kebun Village, Hamparan Perak District - Ritonga, Ristra Sandra; Munisa; Zulfahmi Syahputra; Sabrina Patuzahra (ASIAN PUBLISHER, 2024)
Linguistic intelligence is an important aspect that should be nurtured from an early age, as it serves as the primary tool for interacting and communicating with others. Language disorders can be categorized in various ways, one of which is speech delay. Speech delay occurs when a child struggles to express their wishes or thoughts to others, often resulting in unclear speech and a limited vocabulary compared to their peers. The research was conducted in Klambir V Kebun Village, Hamparan Perak District, Deli Serdang Regency, North Sumatra. The study aimed to design a speech therapy e-module with music therapy method. This research procedure adapts the ADDIE development model which consists of five stages including analysis, design, development, implementation, and evaluation. Based on the results of the validity test conducted with two validators, namely with media expert lecturers and material experts in each field. With the results of the validity test on the media getting a percentage of 83%, and on the material expert validation percentage of 78%. From the results of these two validations, the e-module of speech therapy with the music therapy method can be said to be feasible without revision to be tested in early childhood. Based on the results of the practical test, it can be concluded that the e-module of speech therapy with music therapy methods to alleviate speech delay problems in early childhood gets a score of 207 with a percentage of feasibility of 78%. So that children feel there is a new media used to sing.